New Clues on the Origin of the "Inca Mirror" at the Museum National d'Histoire Naturelle in Paris. Issue 2 (June 2019) - Calligaro, Thomas; Chiappero, Pierre-Jacques; Gendron, François; Poupeau, Gérard
Abstract : Since at least 1742, the mineralogical collection of the Muséum National d'Histoire Naturelle (MNHN) in Paris has hosted, under the reference number 22.U, a biconvex lens-shaped obsidian artifact, also described as a mirror, measuring 250 mm in diameter and finely polished on both faces. It has usually been ascribed to the shipment sent by Hernán Cortez in 1522 to the Emperor Charles V, which was captured by a French privateer. We investigated the object using modern techniques. The elemental composition of the obsidian determined by the particle induced X-ray emission (PIXE) method showed that the raw material originates from the Mullumica deposit (Ecuador). Documentary investigations revealed that the lens (renumbered No. 176.101) was sent in 1737 from Quito, Ecuador (at that time part of the viceroyalty of Peru), to France by members of the Godin–La Condamine geodesic expedition (1735–1743). The mirror is thus among the rare Ecuadorian archeological or colonial artifacts to have reached the Old World during the eighteenth century. Abstract : La colección de mineralogía del Museum National d'Histoire Naturelle (MNHN) de París conserva desde 1742 una lente de obsidiana (n.° 22.U; Ø: 250 mm) finamente pulida en ambos lados. Tradicionalmente fue atribuida a los objetos enviados en 1522 al emperador Carlos V por Hernán Cortés y capturados por un corsario francés. A partir del re-estudio del material de archivo se consideró la necesidad de realizar un análisis de la obsidiana con técnicas modernas. La composición elemental de la obsidiana, determinada por espectrometría de rayos X inducida por partículas (PIXE), permitió establecer que proviene del yacimiento de Mullumica (Ecuador). Asimismo, los documentos revelan el envío de este espejo en 1737 desde Quito (en ese momento Ecuador era parte del Virreinato del Perú) a Francia por los miembros de la expedición geodésica Godin - La Condamine (1735–1743). En consecuencia, dicha lente (renumerada 176.101) constituye uno de los raros objetos arqueológicos o coloniales ecuatorianos que han alcanzado el "Viejo Mundo" durante el siglo dieciocho.